Physical responses of professional soccer players during 4 vs. 4 small-sided games with mini-goals according to rule changes - Giménez, Jesús V.; Liu, Hongyou; Lipińska, Patrycja; Szwarc, Andrzej; Rompa, Paweł; Gómez, Miguel A. (Biology of Sport, 2018)
The aim of this study was to investigate the influence of the number of ball touches authorised per game (one touch [T1], two touches [T2], and free touches [FT]) on the players’ physical responses throughout the bouts in 4 vs 4 soccer small-sided games (SSGs) with mini-goals (without a goalkeeper). Fourteen professional Polish players (age 23.2±2.7 years, height 177.9±6.1 cm, weight: 73.2±6.9 kg, body fat 12.6±2%, playing experience: 14±5 years) completed nine series of 4 vs 4 SSGs. Each trial included three series of SSGs with a game duration of 4 minutes on an equal sized pitch (30x24 m; 720 m2; individual occupied area per player=90 m2). Differences in physical responses and time-motion characteristics of players were measured with the Global Positioning System (GPS) and assessed using a repeated measures ANOVA to compare the three game conditions and the magnitude-based inference to evaluate the pairwise comparison effects. The results showed that only the variables distance covered at low speed, time walking, time at low speed, and accelerations of >4 m/s² were statistically significantly different among game conditions. The pairwise comparisons only identified significant effects for distance covered at low speed (between FT and T2), for time walking (between FT and T1), for time at moderate and low speed (between FT and T2), and for accelerations of >4 m/s² (between FT and T1). The players’ performances are affected by the ball touch constraint during SSGs with mini-goals. The results provide useful information for training and task design that replicate specific physical demands (i.e., accelerations of >4 m/s², time walking or running at a lower speed).